PEMANFAATAN LEARNING MANAGEMENT SYSTEM (LMS) DALAM PENDIDIKAN JASMANI UNTUK PENGELOLAAN MATERI DAN TUGAS - Syafruddin, Akbar; Alimin Hamzah (Jurnal Teknologi Pendidikan, 2025)
This study uses a qualitative descriptive approach with the aim of understanding and describing how lecturers utilize the Learning Management System (LMS) in managing materials and assignments in physical education courses. This research was conducted at the Physical Education, Health, and Recreation Study Program, Faculty of Sport Science, Makassar State University. The main instrument in this study was the researcher himself who acted as a data collector and analyst. In addition, interview guidelines, observation sheets, and documentation recording formats were used as tools in data collection. Based on the results of the interview, the use of LMS in physical education has provided many benefits, especially in terms of managing materials and assignments. However, practical learning still requires further innovation to ensure that a holistic learning experience can be achieved. Therefore, the integration of LMS with other learning methods, such as blended learning, can be a potential solution to improve the effectiveness of physical education learning in the future.